1998
DOI: 10.1177/107110079801901005
|View full text |Cite
|
Sign up to set email alerts
|

Support of the Talus: A Biomechanical Investigation of the Contributions of the Talonavicular and Talocalcaneal Joints, and the Superomedial Calcaneonavicular Ligament

Abstract: The goal of this study was to determine the magnitude of force transmission to the talus by its inferior articulations to provide insight into mechanisms involving acquired deformities of the hindfoot. Cadaver feet were mounted in a loading apparatus that applied axial force through the tibia and fibula as well as tensile loading of the tendons of extrinsic musculature. This also permitted positioning of the tibia in the sagittal plane. Eighteen specimens were tested in three selected positions of the gait cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…For the subtalar joint (especially the posterior articular surfaces), Mulcahy described a bicentric distribution of the main contact zones, located anterolaterally and posteromedially [17]. Essentially, Wagner and Reeck came to the same conclusion [21,30]. In contrast to these results, Seangeorzan's [23] study also showed a bicentric distribution of high pressure zones but they were located in the anteromedial and posterolateral portions of the articular surfaces.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…For the subtalar joint (especially the posterior articular surfaces), Mulcahy described a bicentric distribution of the main contact zones, located anterolaterally and posteromedially [17]. Essentially, Wagner and Reeck came to the same conclusion [21,30]. In contrast to these results, Seangeorzan's [23] study also showed a bicentric distribution of high pressure zones but they were located in the anteromedial and posterolateral portions of the articular surfaces.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, several studies have investigated the load on these two joints but mainly focused on static and short-term [14,17,21,23,30]. By means of pressuresensitive film the instantaneous load on the articular surfaces was determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The talonavicular and subtalar joints are linked anatomically and functionally. Because three functions (weight acceptance, single limb support, and advancement of the limb [36]) are completed in each gait cycle, locally different contact forces [32] and energy dissipation [36] occur within the hindfoot. With initial weight acceptance and single limb support, energy dissipation has a higher effect on the distal articular surface in our data, mostly on the calcaneal aspect of posterior facet of the subtalar joint.…”
Section: Discussionmentioning
confidence: 99%